Dynamic gene regulatory networks drive seed dormancy and germination of Pinus tabuliformis - Yanjun Li; Duxian Lu; Xinxiu Zuo; Yanyan Zhang; Yufen Bu; Shihui Niu; Jinxing Lin; Yaning Cui (BMC Plant Biology)
Abstract The Pinus tabuliformis (Chinese pine), a keystone conifer species native to northern China with extended distributions into central and southern regions (e.g., Henan), plays a critical role in regional vegetation dynamics. Unraveling the molecular mechanisms underlying its seed dormancy and germination is vital for guiding effective ecological conservation and reforestation efforts. In order to elucidate the germination mechanism of Chinese pine seeds, we performed the transcriptome analysis of dormant seeds (S1), non-dormant seeds (S2), and germinating seeds (S3). We obtained high-quality transcriptome data from seeds at three developmental stages using the Illumina sequencing platform and conducted time-series trend analysis. The results revealed four gene modules significantly associated with the germination of Pinus tabuliformis seeds, alongside 857 DEGs (differentially expressed genes). WGCNA (Weighted Gene Co-expression Network Analysis) further pinpointed a key module comprising 153 genes strongly correlated with germination, of which 24 were prioritized as putative regulators. Expression profiling of 12 representative candidates across developmental stages revealed that at least 7 genes exhibited marked expression shifts during the dormancy-to-germination transition. Notably, PtbZIP25 (Pt4G12300) a homolog of Arabidopsis thaliana bZIP transcription factors, was functionally validated as a negative regulator of germination via overexpression and mutant assays. This gene modulate the expression of dormancy-related markers (DOG1, CYP707A2), indicating its potential role in ABA signaling. Our findings provide novel insights into the molecular basis of conifer seed germination and offer potential targets for optimizing afforestation practices.